Efeitos da Cetamina S(+) em Tartaruga da Amazônia Podocnemis expansa schweigger, 1812 (Testudines Podocnemididae) - Leonardo, Tatiana Grillo (2012)
Aiming to evaluate different protocols of S (+) ketamine and to define the most appropriate dose of this drug for chemical restraint in chelonians, we used 40 specimens of giant Amazon river turtle, with weights ranging from 1.0 to 1.5 kg, from the commercial breeding Moenda da Serra, in Araguapaz - Goiás - Brazil, which were divided into four groups of ten animals. We administered S (+) ketamine in doses of 10 mg/kg, 15 mg/kg, 20 mg/kg and 40 mg/kg, in groups one, two, three and four, respectively, all intramuscularly (IM). We evaluated the physiological parameters of cloacal temperature and heart rate, as well as righting reflex, muscle relaxation (motor block), support the head and response to noxious stimuli (sensory block). The dose of 10 mg/kg did not provide any effect on the animals, being inefficient in pharmacological restraint of P. expansa. With the protocols of 15 mg/kg, 20 mg/kg and 40 mg/kg, all animals exhibited muscle relaxation without loss of righting reflex; maintained at soreness and no statistical differences in relation to heart rate and cloacal temperature. However, the duration of action of the drug was significantly higher in the group that was administered the dose of 40mg/kg IM. It is concluded that the protocol of S (+) ketamine 10 mg/kg IM is not capable of promoting effects in Podocnemis expansa, and that the dose for the pharmacological restraint of the species varies from 15 to 40 mg/kg IM.